ALLOY NANOPARTICLES, METHODS FOR FORMING ALLOY NANOPARTICLES, AND ALLOY NANOCATALYST COMPRISING ALLOY NANOPARTICLES - Patent application

A method for forming alloy nanoparticles using metal complexes and heat-treatment on a carbon support addresses the complexity and cost issues of colloidal synthesis, resulting in nanoparticles with superior electrocatalytic performance.

JP7601355B2Active Publication Date: 2024-12-17SEOUL NATIONAL UNIVERSITY R&DB FOUNDATION +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2022567631
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-05-07
Filing Date
2021-05-07
Publication Date
2024-12-17
Estimated Expiration
2041-05-07

AI Technical Summary

Technical Problem

Colloidal synthesis of alloy nanoparticles is complicated and costly due to the use of toxic and expensive surfactants, and the process is difficult to control in terms of size, composition, and shape, which complicates manufacturing and increases costs.

Method used

A method involving the mixing of first and second metal complexes to form a multimetal compound, followed by heat-treatment and thermal etching to create alloy nanoparticles with a carbon shell, using pyridine-based ligands and a carbon support.

Benefits of technology

The method allows for the easy formation of alloy nanoparticles with excellent activity and stability, suitable for use as electrocatalysts, particularly in oxygen reduction reactions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007601355000001
    Figure 0007601355000001
  • Figure 0007601355000002
    Figure 0007601355000002
  • Figure 0007601355000003
    Figure 0007601355000003
Patent Text Reader

Abstract

Alloy nanoparticles, methods for forming alloy nanoparticles, and alloy nanocatalysts including the alloy nanoparticles are provided. According to an embodiment of the present invention, alloy nanoparticles are formed by a method including the steps of: mixing a first metal complex containing a first metal with a second metal complex containing a second metal to form a multi-metal compound; and heat-treating the multi-metal compound to form an alloy compound. The first metal and the second metal include transition metals, and the first metal complex includes a pyridine-based ligand. The heat-treatment forms a carbon shell containing nitrogen on the surface of the alloy compound.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to alloy nanoparticles, methods for forming said alloy nanoparticles, and alloy nanocatalysts comprising said alloy nanoparticles. [Background technology]

[0002] Alloy nanoparticles have unique electronic and geometric structures and therefore exhibit novel properties that distinguish them from single metal nanoparticles. In particular, they have been actively investigated as fuel cell electrocatalysts because they show improved activity and stability compared to single metal-based catalysts.

[0003] Colloidal synthesis has been widely used to produce alloy nanoparticles because the size, composition and shape can be easily controlled. However, colloidal methods require toxic and expensive surfactants and reducing agents. In addition, further steps such as loading the alloy nanoparticles onto the support and removing the protecting ligands are required.

[0004] Thus, it is difficult to control the size, composition, and shape of the alloy nanoparticles, which not only complicates the manufacturing process but also increases the manufacturing cost. Summary of the Invention [Problem to be solved by the invention]

[0005] The present invention provides alloy nanoparticles with excellent performance. The present invention provides a method for forming said alloy nanoparticles. The present invention provides alloy nanocatalysts with superior performance. Other objects of the present invention will become apparent from the following detailed description and the accompanying drawings. [Means for solving the problem]

[0006] According to an embodiment of the present invention, alloy nanoparticles are formed by a method including the steps of mixing a first metal complex including a first metal and a second metal complex including a second metal to form a multi-metal compound, and heat-treating the multi-metal compound to form an alloy compound, wherein the first metal and the second metal include transition metals, the first metal complex includes a pyridine-based ligand, and the heat-treating forms a N-containing carbon shell on a surface of the alloy compound.

[0007] The pyridine-based ligand includes at least one of a pyridine ligand and a polypyridine ligand, the pyridine ligand includes pyridine and derivatives derived from the pyridine, and the polypyridine ligand includes polypyridine and derivatives derived from the polypyridine.

[0008] The second metal complex contains a halogen element.

[0009] The first metal includes at least one of Fe, Co, and Ni, and the second metal includes Pt.

[0010] The first metal complex is M 1 (PY) m a+ (M 1 represents a first metal, PY represents a pyridine-based ligand, and m represents an integer of 6 or less, and the second metal complex is M 2 X n a- (M 2 represents a second metal, X represents a halogen element, and n represents an integer of 6 or less).

[0011] The first metal complex is [M 1A (PY) m ] x [M 1B (PY) m ] 1-x a+ (M 1A and M 1B each represents a first metal different from the others, PY represents a pyridine-based ligand, and m represents an integer of 6 or less, and the second metal complex is 2 Xn a- (M 2 represents a second metal, X represents a halogen element, and n represents an integer of 6 or less).

[0012] The method further includes subjecting the alloy compound to a thermal etch, the thermal etch removing at least a portion of the shell.

[0013] The heat treatment is carried out after the polymetallic compound is adsorbed onto the carbon support.

[0014] A method for forming alloy nanoparticles according to an embodiment of the present invention includes the steps of mixing a first metal complex containing a first metal and a second metal complex containing a second metal to form a multi-metal compound, adsorbing the multi-metal compound onto a support, and heat-treating the multi-metal compound to form an alloy compound, wherein the first metal and the second metal comprise transition metals, the first metal complex comprises a pyridine-based ligand, and the heat-treating forms a N-containing carbon shell on a surface of the alloy compound.

[0015] The pyridine-based ligand includes at least one of a pyridine ligand and a polypyridine ligand, the pyridine ligand includes pyridine and derivatives derived from the pyridine, and the polypyridine ligand includes polypyridine and derivatives derived from the polypyridine.

[0016] The second metal complex includes a halogen element, the first metal includes at least one of Fe, Co, and Ni, and the second metal includes Pt.

[0017] The first metal complex is M 1 (PY) m a+ (M 1 represents a first metal, PY represents a pyridine-based ligand, and m represents an integer of 6 or less, and the second metal complex is M 2 X n a- (M 2represents a second metal, X represents a halogen element, and n represents an integer of 6 or less).

[0018] The first metal complex is [M 1A (PY) m ] x [M 1B (PY) m ] 1-x a+ (M 1A and M 1B each represents a first metal different from the others, PY represents a pyridine-based ligand, and m represents an integer of 6 or less, and the second metal complex is 2 X n a- (M 2 represents a second metal, X represents a halogen element, and n represents an integer of 6 or less).

[0019] The method of forming the alloy nanoparticles further includes subjecting the alloy compound to a thermal etch, the thermal etch removing at least a portion of the shell.

[0020] The first metal complex and the second metal complex are bonded to each other via electrostatic attraction.

[0021] The polymetallic compound is wetted onto the support by the heat treatment and decomposed into the alloy compound.

[0022] The method for forming alloy nanoparticles further includes freeze-drying the support onto which the multi-metal compound is adsorbed prior to the heat treatment.

[0023] The support includes a carbon support.

[0024] The alloy nanocatalyst according to the embodiment of the present invention comprises the alloy nanoparticles. Effect of the Invention

[0025] The alloy nanoparticles and alloy nanocatalysts according to the embodiments of the present invention may have excellent performance. For example, the alloy nanoparticles and alloy nanocatalysts may have excellent activity and stability. The alloy nanoparticles and alloy nanocatalysts may be easily formed through a simple process. The alloy nanocatalysts have excellent ORR (oxygen reduction reaction) activity and may be used as electrocatalysts. [Brief description of the drawings]

[0026] [Figure 1] A schematic diagram of the formation of aligned FePt alloy nanoparticles supported by reduced graphene oxide (rGO) and with N-containing carbon shells is shown. [Diagram 2] Figure 1 shows a TEM image of [Fe(bpy)3][PtCl6] / GO. [Diagram 3] Figure 1 shows a TEM image of the intermediate. [Figure 4] Figure 1 shows a TEM image of FePt / rGO. [Diagram 5] Powder XRD analysis results of [Fe(bpy)3][PtCl6] / GO, the intermediate, and FePt / rGO are shown. [Figure 6] The FT-IR analysis results of [Fe(bpy)3][PtCl6] / GO, the intermediate, and FePt / rGO are shown. [Figure 7] STEM-EDS mapping images showing uniform distribution of C, Pt, and Fe atoms in the intermediate are shown. [Figure 8] Figure 1 shows the XRD pattern of 37 wt% FePt / rGO. [Figure 9] Figure 1 shows the magnetic hysteresis loop of 37 wt% FePt / rGO. [Figure 10] The HAADF-STEM image and enlarged image of 37 wt% FePt / rGO and the simulated image of L10-FePt nanocrystals are shown. [Figure 11]STEM-EDS images of a single FePt nanoparticle (top) and a higher magnification area of ​​37 wt% FePt / rGO (bottom) are shown. [Figure 12] Figure 1 shows a TEM image of 24 wt%-FePt / rGO, and the inset shows the size distribution of FePt nanoparticles. [Figure 13] Figure 1 shows a TEM image of 37 wt%-FePt / rGO, and the inset shows the size distribution of FePt nanoparticles. [Figure 14] Figure 2 shows the ORR polarization curves of FePt / rGO and Pt / C catalysts. [Figure 15] The Tafel plots of the FePt / rGO and Pt / C catalysts are shown. [Figure 16] The ECSA of the FePt / rGO and Pt / C catalysts is shown. [Figure 17] The activity per unit weight and the activity per unit area of ​​the FePt / rGO catalyst and the Pt / C catalyst are shown. [Figure 18] The ORR polarization curves of FePt / rGO and Pt / C catalysts before and after ADT (20,000 cycles) are shown. [Figure 19] The Tafel plots of FePt / rGO and Pt / C catalysts before and after ADT (20,000 cycles) are shown. [Figure 20] The ECSA of FePt / rGO and Pt / C catalysts before and after ADT (20,000 cycles) is shown. [Figure 21] The activity per unit weight and activity per unit area of ​​the FePt / rGO and Pt / C catalysts before and after ADT (20,000 cycles) are shown. [Figure 22] A TEM image of NiPt / rGO (46 wt%) is shown. [Figure 23] STEM-EDS image of NiPt / rGO (46 wt%) is shown. [Figure 24] A TEM image of CoPt / rGO (22 wt%) is shown. [Diagram 25] STEM-EDS image of CoPt / rGO (22 wt%) is shown. [Figure 26]1 shows the powder XRD patterns of NiPt / rGO and CoPt / rGO. [Figure 27] Figure 2 shows the ORR polarization curves of NiPt / rGO and CoPt / rGO. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0027] The present invention will be described in detail below with reference to the following examples. The objects, features, and advantages of the present invention will be readily understood from the following examples. The present invention is not limited to the embodiments described herein, and may be embodied in other forms. The embodiments described herein are provided so that the disclosed content will be thorough and complete, and will fully convey the concept of the present invention to those skilled in the art to which the present invention pertains. Therefore, the present invention should not be limited by the following examples.

[0028] In this specification, terms such as first, second, etc. are used to describe various elements, but these elements should not be limited by these terms. These terms are used to distinguish these elements from each other.

[0029] According to an embodiment of the present invention, alloy nanoparticles are formed by a method including the steps of mixing a first metal complex including a first metal and a second metal complex including a second metal to form a multi-metal compound, and heat-treating the multi-metal compound to form an alloy compound, wherein the first metal and the second metal include transition metals, the first metal complex includes a pyridine-based ligand, and the heat-treating forms a N-containing carbon shell on a surface of the alloy compound.

[0030] The pyridine-based ligand includes at least one of a pyridine ligand and a polypyridine ligand, the pyridine ligand includes pyridine and a derivative derived from the pyridine, and the polypyridine ligand includes polypyridine and a derivative derived from the polypyridine. The polypyridine may include bipyridine, phenanthroline, terpyridine, quaterpyridine, etc.

[0031] The second metal complex contains a halogen element.

[0032] The first metal includes at least one of Fe, Co, and Ni, and the second metal includes Pt.

[0033] The first metal complex is M 1 (PY) m a+ (M 1 represents a first metal, PY represents a pyridine-based ligand, and m represents an integer of 6 or less, and the second metal complex is M 2 X n a- (M 2 represents a second metal, X represents a halogen element, and n represents an integer of 6 or less).

[0034] The first metal complex is [M 1A (PY) m ] x [M 1B (PY) m ] 1-x a+ (M 1A and M 1B each represents a first metal different from the others, PY represents a pyridine-based ligand, and m represents an integer of 6 or less, and the second metal complex is 2 X n a- (M 2represents a second metal, X represents a halogen element, and n represents an integer of 6 or less. The second metal complex may also be extended to include two or more first metals different from each other, such that M 2 X n a- and can be extended to include two or more different second metals.

[0035] The method further includes subjecting the alloy compound to a thermal etch, the thermal etch removing at least a portion of the shell.

[0036] The heat treatment is performed after the multimetal compound is adsorbed onto a carbon support, which may include graphene oxide.

[0037] A method for forming alloy nanoparticles according to an embodiment of the present invention includes the steps of mixing a first metal complex containing a first metal and a second metal complex containing a second metal to form a multi-metal compound, adsorbing the multi-metal compound onto a support, and heat-treating the multi-metal compound to form an alloy compound, wherein the first metal and the second metal comprise transition metals, the first metal complex comprises a pyridine-based ligand, and the heat-treating forms a N-containing carbon shell on a surface of the alloy compound.

[0038] The pyridine-based ligand may include at least one of a pyridine ligand and a polypyridine ligand, the pyridine ligand may include pyridine and derivatives derived from the pyridine, and the polypyridine ligand may include polypyridine and derivatives derived from the polypyridine. The polypyridine may include bipyridine, phenanthroline, terpyridine, quaterpyridine, etc.

[0039] The second metal complex contains a halogen element.

[0040] The first metal includes at least one of Fe, Co, and Ni, and the second metal includes Pt.

[0041] The first metal complex is M 1 (PY) m a+ (M 1 represents a first metal, PY represents a pyridine-based ligand, and m represents an integer of 6 or less, and the second metal complex is M 2 X n a- (M 2 represents a second metal, X represents a halogen element, and n represents an integer of 6 or less).

[0042] The first metal complex is [M 1A (PY) m ] x [M 1B (PY) m ] 1-x a+ (M 1A and M 1B each represents a first metal different from the others, PY represents a pyridine-based ligand, and m represents an integer of 6 or less, and the second metal complex is 2 X n a- (M 2 represents a second metal, X represents a halogen element, and n represents an integer of 6 or less. The second metal complex may also be extended to include two or more first metals different from each other, such that M 2 X n a- and can be extended to include two or more different second metals.

[0043] The method of forming the alloy nanoparticles further includes subjecting the alloy compound to a thermal etch, the thermal etch removing at least a portion of the shell.

[0044] The first metal complex and the second metal complex are bonded to each other via electrostatic attraction.

[0045] The polymetallic compound is wetted onto the support by the heat treatment and decomposed into the alloy compound.

[0046] The method for forming alloy nanoparticles further includes freeze-drying the support onto which the multi-metal compound is adsorbed prior to the heat treatment.

[0047] The support may include a carbon support. The carbon support may include graphene oxide, etc.

[0048] The alloy nanocatalyst according to the embodiment of the present invention comprises the alloy nanoparticles.

[0049] FIG. 1 shows a schematic diagram of the formation of aligned FePt alloy nanoparticles supported by reduced graphene oxide (rGO) and having a N-containing carbon shell, FIG. 2 shows a TEM image of [Fe(bpy)3][PtCl6] / GO in FIG. 1, FIG. 3 shows a TEM image of the intermediate in FIG. 1, and FIG. 4 shows a TEM image of FePt / rGO in FIG. 1.

[0050] Referring to FIG. 1 to FIG. 4, FePt alloy nanoparticles can be formed through two main steps. First, cationic Fe(bpy)3 2+ Equimolar anionic PtCl6 to the complex 2- Due to the electrostatic attraction between the complexes, a bimetallic [Fe(bpy)3][PtCl6] compound (represented as FePt compound) is formed. In the second step, the FePt compound adsorbed on the graphene oxide can be directly converted into bimetallic alloy nanoparticles by annealing at 700 °C.

[0051] Pale yellow aqueous FeSO4 is Fe(bpy)3 2+ When 2,2'-bipyridine (bpy) is added to form the complex, the color immediately changes to dark red. The Fe(bpy)3SO4 salt is highly crystalline and the Fe(bpy)3 2+ It has UV-vis (ultraviolet-visible) light absorption properties derived from this.

[0052] When ethanolic H2PtCl6 is added to Fe(bpy)3SO4 solution, the FePt compound precipitates rapidly and can be easily obtained as fine powder by pulverization after centrifugation. The atomic ratio of Fe to Pt is close to 1:1 at five different sites, which can be clearly confirmed by STEM (scanning transmission electron microscopy)-EDS (energy-disperse X-ray spectroscopy).

[0053] According to the powder XRD analysis, the FePt compound has a completely different crystal structure and high crystallinity from the Fe(bpy)3SO4 salt. Based on the UV-vis absorption spectrum of the aqueous FePt compound, the Fe(bpy)3 2+ and PtCl6 2- The presence of the complexes and the electrostatic attraction between them were analyzed. The absorption characteristics of both complexes confirm the presence of anionic and cationic complexes, but the significant red-shift of the 524 nm peak to 538 nm indicates an electrostatic attraction between them. Conversely, successive dilutions of the FePt compound cause a peak shift from 538 nm to 524 nm, indicating a weakening of the electrostatic attraction between the Fe and Pt complexes.

[0054] The FePt compound is adsorbed onto the GO surface in deionized water and then freeze-dried to prevent excessive deposition of the GO layer. The mixture is then heated to 700°C, during which the FePt compound completely wets and decomposes onto the GO, forming bimetallic alloy nanoparticles.

[0055] [Synthesis example of FePt compound] 1) First synthesis example Dissolve 0.5 mmol of FeSO4·7H2O in 15 mL of deionized water (DI) (or 15 mL of ethanol) and dissolve 1.5 mmol of 2,2'-bipyridine in 15 mL of ethanol (99.9%) separately. Mix both solutions to form [Fe(bpy)3]SO4 (bpy stands for 2,2'-bipyridine) and stir at room temperature. Add 0.5 mmol of H2PtCl6·6H2O in 30 mL of ethanol at once to this solution and stir for 5 h. The product is easily separated by centrifugation at 10,000 rpm (10 min). Wash the product several times with ethanol, centrifuge and then dry in an oven at 40 °C. Grind the dried product to obtain a fine powder. This forms the FePt compound ([Fe(bpy)3][PtCl6]).

[0056] 2) Second synthesis example Dissolve 0.5 mmol of FeSO4·7H2O in 15 mL of deionized water (DI) (or 15 mL of ethanol) and dissolve 1.5 mmol of phenanthroline in 15 mL of ethanol (99.9%) separately. Mix both solutions to form [Fe(phen)3]SO4 (phen stands for phenanthroline) and stir at room temperature. Add 0.5 mmol of H2PtCl6·6H2O in 30 mL of ethanol at once to this solution and stir for 5 h. The product is easily separated by centrifugation at 10,000 rpm (10 min). Wash the product several times with ethanol, centrifuge and then dry in an oven at 40 °C. Grind the dried product to obtain a fine powder. This forms the FePt compound ([Fe(phen)3][PtCl6]).

[0057] 3) Third Synthesis Example Dissolve 0.5 mmol of FeSO4·7H2O in 15 mL of deionized water (DI) (or 15 mL of ethanol) and dissolve 1.0 mmol of terpyridine in 15 mL of ethanol (99.9%) separately. Mix both solutions to form [Fe(terpy)2]SO4 (terpy stands for terpyridine) and stir at room temperature. Add 0.5 mmol of H2PtCl6·6H2O in 30 mL of ethanol at once to this solution and stir for 5 h. The product is easily separated by centrifugation at 10,000 rpm (10 min). Wash the product several times with ethanol, centrifuge and then dry in an oven at 40 °C. Grind the dried product to obtain a fine powder. This forms the FePt compound ([Fe(terpy)2][PtCl6]).

[0058] [Synthesis example of FePt / rGO] The FePt compound (36 mg and 144 mg of FePt compound for FePt loading of about 24 wt% and 37 wt% respectively) is dispersed in 80 mL of deionized water. The mixture with dispersed FePt compound is sonicated for 10 min and stirred for 2 h, after which 10 mL of GO aqueous solution (4 mg / mL) is added dropwise. The mixture with added GO aqueous solution is stirred for 2 h and then freeze-dried to adsorb the FePt compound onto the GO. The mixture containing the FePt compound grains on the GO foam is heat-treated at 700 °C for 6 h in 100 sccm argon flow, during which wetting and decomposition of the FePt compound occurs on the GO surface and atomically aligned FePt alloy nanoparticles (FePt / rGO) are formed on the rGO.

[0059] [Examples of synthesis of FePt nanoparticles on other carbon supports] The synthesis of FePt nanoparticles on carbon nanotubes (CNTs, 7–8 wt% in water) is carried out in a similar manner to FePt / rGO, except that a CNT aqueous solution is dropped instead of a GO solution.

[0060] The synthesis of FePt nanoparticles on Ketjen Black (KB) and Vulcan XC (VC) is carried out in the following manner: A certain amount of FePt compound is dispersed in 80 mL of isopropanol (or ethanol), and the solution is then sonicated for 10 min and stirred for 2 h. 50 mg of KB or VC powder is added to the solution containing the FePt compound, and the mixture is sonicated for 10 min and then stirred for 2 h. A mixture containing FePt compound grains on a carbon support is obtained by rotary evaporation and dried in an oven at 40 °C. The dried powder is ground and then heat-treated at 700 °C under an argon atmosphere.

[0061] [Synthesis of CoPt and NiPt nanoparticles on rGO] CoPt compounds (e.g., [Co(bpy)3][PtCl6], [Co(phen)3][PtCl6], [Co(terpy)2][PtCl6]) and NiPt compounds (e.g., [Ni(bpy)3][PtCl6], [Ni(phen)3][PtCl6], [Ni(terpy)2][PtCl6]) can be formed in a similar manner to the synthesis of FePt compounds, except that CoSO4·7H2O and NiSO4·6H2O were used instead of FeSO4·7H2O. The subsequent steps for the synthesis of CoPt / rGO and NiPt / rGO are the same as those for the synthesis of FePt / rGO.

[0062] [Synthesis example of FeCoPt compound] 1) First synthesis example Dissolve 0.25 mmol of FeSO4·7H2O in 7.5 mL of deionized water (DI) (or 7.5 mL of ethanol) and dissolve 0.75 mmol of 2,2'-bipyridine in 7.5 mL of ethanol (99.9%) separately. Mix both solutions to form [Fe(bpy)3]SO4 (bpy stands for 2,2'-bipyridine) and stir at room temperature. Dissolve 0.25 mmol of CoSO4·7H2O in 7.5 mL of deionized water (DI) (or 7.5 mL of ethanol) and dissolve 0.75 mmol of 2,2'-bipyridine in 7.5 mL of ethanol (99.9%) separately. Mix both solutions to form [Co(bpy)3]SO4 and stir at room temperature.

[0063] The [Fe(bpy)3]SO4 solution and the [Co(bpy)3]SO4 solution are mixed, and 30 mL of ethanol solution containing 0.5 mmol of H2PtCl6·6H2O is added to the solution at once and stirred for 5 hours. The product is easily separated by centrifugation at 10,000 rpm (10 min). The product is washed several times with ethanol, centrifuged, and then dried in an oven at 40 °C. The dried product is ground to obtain a fine powder. This results in the FeCoPt compound ([Fe(bpy)3] x [Co(bpy)3] 1-x [PtCl6]) is formed.

[0064] 2) Second synthesis example Dissolve 0.25 mmol of FeSO4 7H2O in 7.5 mL of deionized water (DI) (or 7.5 mL ethanol) and dissolve 0.75 mmol of phenanthroline in 7.5 mL of ethanol (99.9%) separately. Mix both solutions to form [Fe(phen)3]SO4 (phen stands for phenanthroline) and stir at room temperature. Dissolve 0.25 mmol of CoSO4 7H2O in 7.5 mL of deionized water (DI) (or 7.5 mL ethanol) and dissolve 0.75 mmol of phenanthroline in 7.5 mL of ethanol (99.9%) separately. Mix both solutions to form [Co(phen)3]SO4 and stir at room temperature.

[0065] The [Fe(phen)3]SO4 solution and the [Co(phen)3]SO4 solution are mixed, and 30 mL of ethanol solution containing 0.5 mmol of H2PtCl6·6H2O is added to the solution at once and stirred for 5 hours. The product is easily separated by centrifugation at 10,000 rpm (10 min). The product is washed several times with ethanol, centrifuged, and then dried in an oven at 40°C. The dried product is ground to obtain a fine powder. This gives the FeCoPt compound ([Fe(phen)3] x [Co(phen)3] 1-x [PtCl6]) is formed.

[0066] 3) Third synthesis example Dissolve 0.25 mmol of FeSO4·7H2O in 7.5 mL of deionized water (DI) (or 7.5 mL ethanol) and dissolve 0.5 mmol of terpyridine in 7.5 mL of ethanol (99.9%) separately. Mix both solutions to form [Fe(terpy)2]SO4 (terpy stands for terpyridine) and stir at room temperature. Dissolve 0.25 mmol of CoSO4·7H2O in 7.5 mL of deionized water (DI) (or 7.5 mL ethanol) and dissolve 0.5 mmol of terpyridine in 7.5 mL of ethanol (99.9%) separately. Mix both solutions to form [Co(terpy)2]SO4 and stir at room temperature.

[0067] The [Fe(terpy)2]SO4 solution and the [Co(terpy)2]SO4 solution are mixed, and 30 mL of ethanol solution containing 0.5 mmol of H2PtCl6·6H2O is added to the solution at once and stirred for 5 hours. The product is easily separated by centrifugation at 10,000 rpm (10 min). The product is washed several times with ethanol, centrifuged, and then dried in an oven at 40°C. The dried product is ground to obtain a fine powder. This results in the FeCoPt compound ([Fe(terpy)2] x [Co(terpy)2] 1-x [PtCl6]) is formed.

[0068] Unlike the first to third synthesis examples above, FeSO4·7H2O and CoSO4·7H2O can be dissolved in deionized water (or ethanol), and then a solution containing a pyridine compound can be added to this solution. For example, 0.25 mmol of FeSO4·7H2O and 0.25 mmol of CoSO4·7H2O can be dissolved in 15 mL of deionized water (or 15 mL of ethanol), and 1.5 mmol of 2,2'-bipyridine (or 1.5 mmol of phenanthroline, 1.0 mmol of terpyridine) can be dissolved separately in 15 mL of ethanol, and then the two solutions can be mixed. The subsequent steps are the same as those of the first to third synthesis examples above.

[0069] [Synthesis example of FeCoPt / rGO] The FeCoPt compound is dispersed in 80 mL of deionized water. The mixture in which the FeCoPt compound is dispersed is sonicated for 10 min and stirred for 2 h, after which 10 mL of GO aqueous solution (4 mg / mL) is added dropwise. The mixture to which the GO aqueous solution is added is stirred for 2 h, and then freeze-dried to adsorb the FeCoPt compound onto the GO. The mixture containing the FeCoPt compound grains on the GO foam is heat-treated at 700 °C for 6 h in a 100 sccm argon flow, during which wetting and decomposition of the FeCoPt compound occurs on the GO surface during the heat treatment, forming atomically aligned FeCoPt alloy nanoparticles (FeCoPt / rGO) on the rGO.

[0070] [Examples of synthesis of FeCoPt nanoparticles on other carbon supports] The synthesis of FeCoPt nanoparticles on carbon nanotubes (CNTs, 7–8 wt% in water) is carried out in a similar manner to FeCoPt / rGO, except that a CNT aqueous solution is dropped instead of a GO solution.

[0071] The synthesis of FeCoPt nanoparticles on Ketjen Black (KB) and Vulcan XC (VC) is carried out in the following manner: A certain amount of FeCoPt compound is dispersed in 80 mL of isopropanol (or ethanol), and the solution is then sonicated for 10 min and stirred for 2 h. 50 mg of KB or VC powder is added to the solution containing the FeCoPt compound, and the mixture is sonicated for 10 min and then stirred for 2 h. A mixture containing FeCoPt compound grains on a carbon support is obtained by rotary evaporation and dried in an oven at 40 °C. The dried powder is ground and then heat-treated at 700 °C under an argon atmosphere.

[0072] [Synthesis of FeCoPt and CoNiPt nanoparticles on rGO] The FeNiPt compounds (e.g., [Fe(bpy)3]) were prepared in a similar manner to the synthesis of the FeCoPt compounds, except that FeSO4·7H2O and NiSO4·6H2O or CoSO4·7H2O and NiSO4·6H2O were used instead of FeSO4·7H2O and CoSO4·7H2O. x [Ni(bpy)3] 1-x [PtCl6], [Fe(phen)3] x [Ni(phen)3] 1-x [PtCl6], [Fe(terpy)2] x [Ni(terpy)2] 1-x [PtCl6]) and CoNiPt compounds (e.g., [Co(bpy)3] x [Ni(bpy)3] 1-x [PtCl6], [Co(phen)3] x [Ni(phen)3] 1-x [PtCl6], [Co(terpy)2] x [Ni(terpy)2] 1-x [PtCl6]) can be formed. The subsequent steps for the synthesis of FeNiPt / rGO and CoNiPt / rGO are the same as that of FeCoPt / rGO.

[0073] Figure 5 shows the powder XRD analysis results of [Fe(bpy)3][PtCl6] / GO, the intermediate, and FePt / rGO, Figure 6 shows the FT-IR analysis results of [Fe(bpy)3][PtCl6] / GO, the intermediate, and FePt / rGO, and Figure 7 shows the STEM-EDS mapping image showing the uniform distribution of C, Pt, and Fe atoms in the intermediate.

[0074] Referring to FIG. 5, the intermediate obtained at about 500° C. exhibits a smooth surface with no crystalline features of the FePt compound in the XRD pattern.

[0075] Referring to FIG. 6, Fourier transform infrared spectroscopy (FT-IR) provides further structural information of the intermediates indicating decomposition of the bipyridine ligand along with the evolution of the CO and C═C functional groups.

[0076] Referring to FIG. 7, STEM-EDS mapping clearly shows the uniform decomposition of FePt compounds in GO. Uniformly sized alloy nanoparticles are observed without significant aggregation, as confirmed by TEM and SEM (scanning electron microscopy) images. N-containing carbon shells on the nanoparticle surface are identified by high-resolution STEM and TEM images. The carbon shells can be derived from bipyridine ligands and act as protective shells, contributing to the uniform and stable growth of alloy nanoparticles during heat treatment at 700°C.

[0077] Figure 8 shows the XRD pattern of 37 wt% FePt / rGO, Figure 9 shows the magnetic hysteresis loop of 37 wt% FePt / rGO, Figure 10 shows the HAADF-STEM image and magnified image of 37 wt% FePt / rGO and the simulated image of L10-FePt nanocrystals, and Figure 11 shows the STEM-EDS image of a single FePt nanoparticle (top) and a high magnification area (bottom) of 37 wt% FePt / rGO.

[0078] 8 and 9, the crystal structure of FePt nanoparticles can be evaluated through powder XRD analysis and magnetic analysis. The XRD peaks of FePt nanoparticles are in good agreement with the XRD peaks of L10-FePt and are clearly different from other phases such as Fe, Pt, L12-Fe3Pt and L12-FePt3. In addition, ferromagnetism is identified in L10-FePt by a high coercive force of 22.5 kOe at room temperature.

[0079] Referring to Figure 10, the layered atomic arrangement along the (001) plane of the L10-FePt nanoparticles is clearly distinguished with a large difference between Fe and Pt atoms. The FFT (fast Fourier transform) pattern of the atomic image also shows that a face-centered tetragonal crystal structure is evident on the L10-FePt.

[0080] 11, the uniform distribution of Fe and Pt atoms in the FePt nanoparticles is revealed by EDS single particle mapping, and the magnified EDS mapping shows a layer-by-layer distribution of Fe and Pt atoms.

[0081] Therefore, the uniform 1:1 Fe to Pt atomic ratio of the FePt compound is maintained in an atomically ordered manner after the formation of alloy nanoparticles on rGO, as demonstrated by XRD, magnetic measurements, HAADF-STEM imaging, and EDS mapping.

[0082] Figure 12 shows a TEM image of 24 wt%-FePt / rGO, and Figure 13 shows a TEM image of 37 wt%-FePt / rGO. The insets in Figures 12 and 13 show the size distribution of FePt nanoparticles.

[0083] FIG. 14 shows the ORR polarization curves of the FePt / rGO and Pt / C catalysts, and FIG. 15 shows the Tafel plots of the FePt / rGO and Pt / C catalysts.

[0084] 14 and 15, the FePt / rGO catalyst exhibits excellent ORR activity, and the reaction current densities calculated from the Koutechy-Levich equation are compared in Tafel plots. In all regions, the L10-FePt alloy nanoparticles of FePt / rGO show higher reaction current densities than Pt / C.

[0085] FIG. 16 shows the ECSA of the FePt / rGO and Pt / C catalysts, and FIG. 17 shows the activity per unit weight and activity per unit area of ​​the FePt / rGO and Pt / C catalysts.

[0086] Referring to FIG. 16, the electrochemical surface area (ECSA) value calculated based on the oxidation charge of the CO molecule was upd The results were compared with those based on ECSA. CO The values ​​are 53.4 and 45.7 m for 24 wt%-FePt / rGO and 37 wt%-FePt / rGO. 2 / g Pt which are 32 and 41% lower than Pt / C, respectively, due to the larger particle size.

[0087] Referring to FIG. 17, the activities per unit weight of 24 wt%-FePt / rGO and 37 wt%-FePt / rGO at 0.9 V were 1.18 and 1.96 A / mg Pt which are 6.9 and 11.5 times higher than commercial Pt / C, respectively. Despite a 15% lower ECSA value, the activity per unit weight of 37 wt%-FePt / rGO is 66% higher than that of 24 wt%-FePt / rGO. This may be due to the higher level of Fe-Pt atomic alignment in 37 wt%-FePt / rGO. The improved ORR activity on the Pt alloy surface is attributed to the enhanced electronic interaction between Pt and transition metal atoms.

[0088] In 37 wt%-FePt / rGO, the high level of atomic alignment maximizes the ligand effect between Pt and Fe, which can much increase the ORR activity per unit area. The activities per unit area of ​​24 wt%-FePt / rGO and 37 wt%-FePt / rGO at 0.9 V are 2.21 and 4.1 mA / cm. Pt 2 , which are 10.2 and 18.8 times higher than commercial Pt / C, respectively.

[0089] FIG. 18 shows the ORR polarization curves of FePt / rGO and Pt / C catalysts before and after ADT (20,000 cycles), FIG. 19 shows the Tafel plots of FePt / rGO and Pt / C catalysts before and after ADT (20,000 cycles), FIG. 20 shows the ECSA of FePt / rGO and Pt / C catalysts before and after ADT (20,000 cycles), and FIG. 21 shows the activity per unit weight and activity per unit area of ​​FePt / rGO and Pt / C catalysts before and after ADT (20,000 cycles).

[0090] 18 to 21, to evaluate the long-term stability of FePt / rGO, an accelerated degradation test (ADT) was performed by cycling the electrode between 0.6 and 1.0 V for 20,000 cycles under Ar saturated conditions. After ADT, FePt / rGO showed little change in the CV curve, whereas the H of Pt / C was significantly higher than that of Pt / C. updThe area is significantly reduced. The strong stability of FePt / rGO compared to Pt / C can also be confirmed by the ORR polarization curves and Tafel plots. After ADT, the ECSA of Pt / C decreased by 30%, while that of FePt / rGO sample increased slightly by 4-7%. In terms of activity per unit weight and activity per unit area, Pt / C shows a serious drop of 60% and 44%, respectively, after ADT. However, the activity per unit weight of FePt / rGO increases slightly, while the activity per unit area remains almost unchanged after ADT. TEM analysis and EDS mapping for three different sites could further confirm the stability of FePt nanoparticles under harsh ADT conditions that cause particle-particle aggregation and Fe-dissolution. Therefore, the N-containing carbon shell and the high degree of interatomic arrangement inside the FePt nanoparticles are the main factors contributing to the stability of FePt / rGO nanocatalysts synthesized by the embodiments of the present invention.

[0091] Figure 22 shows the TEM image of NiPt / rGO (46 wt%), Figure 23 shows the STEM-EDS image of NiPt / rGO (46 wt%), Figure 24 shows the TEM image of CoPt / rGO (22 wt%), Figure 25 shows the STEM-EDS image of CoPt / rGO (22 wt%), Figure 26 shows the powder XRD patterns of NiPt / rGO and CoPt / rGO, and Figure 27 shows the ORR polarization curves of NiPt / rGO and CoPt / rGO.

[0092] Referring to FIG. 22 to FIG. 27, [Fe(bpy)3] 2+ Instead of [Ni(bpy)3] 2+ or [Co(bpy)3] 2+ can be used to form other platinum alloy nanoparticles.

[0093] The NiPt and CoPt compounds were pyrolyzed to NiPt and CoPt nanoparticles, respectively, on rGO under the same annealing conditions as the FePt compound. TEM and STEM-EDS images of NiPt / rGO and CoPt / rGO showed that NiPt and CoPt alloy nanocrystals were uniformly formed on rGO, similar to the case of FePt / rGO. The bimetallic alloy structure was confirmed by XRD patterns, and the ORR activities of NiPt / rGO (46 wt%) and CoPt / rGO (22 wt%) were determined to be excellent.

[0094] Specific examples of the present invention have been discussed above. Those skilled in the art will understand that the present invention can be embodied in modified forms without departing from the essential characteristics of the present invention. Therefore, the disclosed embodiments should be considered in an illustrative rather than restrictive sense. The scope of the present invention is defined in the claims, not in the above description, and all differences within the scope of the claims should be interpreted as being included in the present invention. [Industrial Applicability]

[0095] The alloy nanoparticles and alloy nanocatalysts according to the embodiments of the present invention may have excellent performance. For example, the alloy nanoparticles and alloy nanocatalysts may have excellent activity and stability. The alloy nanoparticles and alloy nanocatalysts may be easily formed through a simple process. The alloy nanocatalysts have excellent ORR (oxygen reduction reaction) activity and may be used as electrocatalysts.

Claims

1. combining a first metal complex comprising a first metal with a second metal complex comprising a second metal to form a multimetal compound; Adsorbing the polymetallic compound onto a support; and heat treating the multi-metal compound to form an alloy compound; the first metal and the second metal include transition metals; the first metal complex comprises a pyridine-based ligand; A method for forming alloy nanoparticles, characterized in that a carbon shell containing N is formed on a surface of the alloy compound by the heat treatment, The first metal complex comprises M 1 (PY) m a+ (M 1 represents a first metal, PY represents a pyridine-based ligand, and m represents an integer of 6 or less); The method for forming alloy nanoparticles, wherein the second metal complex contains M 2 X n a- (M 2 represents a second metal, X represents a halogen element, and n represents an integer of 6 or less).

2. A method for producing a polymetallic compound comprising: mixing a first metal complex comprising a first metal and a second metal complex comprising a second metal; Adsorbing the polymetallic compound onto a support; and heat treating the multi-metal compound to form an alloy compound; the first metal and the second metal include transition metals; the first metal complex comprises a pyridine-based ligand; A method for forming alloy nanoparticles, characterized in that a carbon shell containing N is formed on a surface of the alloy compound by the heat treatment, The first metal complex is 1A (PY) m ] x [M 1B (PY) m ] 1-x a+ (M 1A and M. 1B represent first metals different from each other, PY represents a pyridine ligand, and m represents an integer of 6 or less, The second metal complex is M 2 X n a- (M 2 represents a second metal, X represents a halogen element, and n represents an integer of 6 or less.

3. A method for producing a polymetallic compound comprising: mixing a first metal complex comprising a first metal and a second metal complex comprising a second metal; Adsorbing the polymetallic compound onto a support; and heat treating the multi-metal compound to form an alloy compound; the first metal and the second metal include transition metals; the first metal complex comprises a pyridine-based ligand; A method for forming alloy nanoparticles, characterized in that a carbon shell containing N is formed on a surface of the alloy compound by the heat treatment, The method for forming alloy nanoparticles, wherein the first metal complex and the second metal complex are bonded to each other via electrostatic attraction.

4. The method of claim 3 , wherein the second metal complex contains a halogen element.

5. the pyridine-based ligand comprises at least one of a pyridine ligand and a polypyridine ligand; The pyridine ligand includes pyridine and derivatives derived from the pyridine; 4. The method of claim 1, wherein the polypyridine ligand comprises a polypyridine and a derivative derived from the polypyridine.

6. the first metal includes at least one of Fe, Co, and Ni; The method for forming alloy nanoparticles according to claim 1 , wherein the second metal includes Pt.

7. further comprising the step of subjecting the alloy compound to a thermal etch; 4. The method of claim 1, wherein the shell is at least partially removed by the thermal etching.

8. 4. The method for forming alloy nanoparticles according to claim 1, wherein the polymetallic compound is wetted onto the support by the heat treatment and decomposed into the alloy compound.

9. 4. The method for forming alloy nanoparticles according to claim 1, further comprising the step of freeze-drying the support on which the multi-metal compound is adsorbed before the heat treatment.

10. 4. The method of claim 1, wherein the support comprises a carbon support.

Citation Information

Patent Citations

  • Caged nanoparticle electrocatalyst with high stability and gas transport property

    JP2016154135A

  • METHOD FOR PRODUCING ALLOY PARTICLES INCLUDING Bi AND Te

    JP2017014578A

  • Polymetallic precursors and compositions and methods for making supported polymetallic nanocomposites

    US6232264B1